Pengaruh Small Sided Games dan Rondo Terhadap Kemampuan Passing Futsal MAN Tegal - Moh Iqbal Al Fian; Martin Sudarmono; Mohamad Annas; Moch Fahmi Abdulaziz (Universitas Negeri Semarang, 2024)
The background in this study is that most of the MAN Tegal City futsal extracurricular participants have a low level of passing accuracy. This type of research is quantitative, the research design used is an experiment using quantitative descriptive data analysis. The purpose of this study is to find out which exercises are good to apply to passing accuracy. The research location was in the South Tegal Sports Building with 14 meetings with the instruments used in this study, namely the passing accuracy test. The results of this study are from 24 samples using total sampling in MAN Tegal City futsal extracurriculars. Based on the results of the study, it was shown that the small side games training was higher than the Rondo exercise, it can be seen that the average score obtained in the Small Sided Games training was 6.42 with an increase of 40.17%, while for the Rondo training it was 5.33 with an increase of 20.59%. Based on the results of the study, it can be concluded that Small Sided Gamestraining is better to improve the passing accuracy results in the MAN Tegal City futsal extracurricular, compared to using Rondo training. The research in this thesis is based on improving the ability of passing accuracy through repetitive and regular practice which ultimately has a significant influence on players.